IMPROVING ENVIRONMENTAL AWARENESS THROUGH A PARTICIPATORY FIELDWORK - Alviani - Permata (Jurnal Pendidikan Karakter, 2021)
This study aims to analyze the provision of field assignments for students to increase their awareness of the environment. This research is an analysis of students' assignments on fieldwork. This fieldwork was an assignment of a course called Ilmu Kealaman Dasar (Basic Natural Science), Faculty of Bussiness, Chirstian Duta Wacana University. This course aimed to enable students to increase their understanding and concern for the natural environment. Lecturing with a teachercentered approach is believed to be unable to achieve the expected lecture goals. Therefore, this approach needs to change by implementing a participative learning strategy. The implementation of this strategy involves students' participation in some activities. Thus, students can comprehend more of the course materials and enthusiastic in their learning process. This work used a text analysis approach by examining the results of student reflections on the vegetable planting process in an organic farm. From the data analysis, it can be seen that there is an increase in students' awareness and concern for the natural environment after they do fieldwork and there are hopes to participate in its maintenance.MENINGKATKAN KESADARAN TERHADAP LINGKUNGAN MELALUI TUGAS LAPANGAN YANG PARTISIPATORIS Penelitian ini bertujuan untuk menganalisis pemberian tugas lapangan bagi mahasiswa untuk peningkatan kesadarannya terhadap lingkungan. Penelitian ini merupakan analisis tugas lapangan mahasiswa. Kerja lapangan ini merupakaan tugas mata kuliah Ilmu Kealaman Dasar mahasiswa Fakultas Bisnis di Universitas Kristen Duta Wacana. Mata kuliah ini bertujuan agar mahasiswa dapat meningkatkan pemahaman dan kepeduliannya terhadap lingkungan alam. Perkuliahan dengan pendekatan berpusat pada guru diyakini tidak dapat mencapai tujuan perkuliahan yang diharapkan. Oleh karena itu, pendekatan ini perlu diubah dengan menerapkan strategi pembelajaran yang partisipatif. Penerapan strategi ini melibatkan partisipasi mahasiswa dalam beberapa kegiatan. Dengan demikian mahasiswa dapat lebih memahami materi perkuliahan dan lebih antusias dalam proses pembelajaran. Penelitian ini menggunakan analisis teks berupa analisis Sarana Tanda dengan menelaah hasil refleksi mahasiswa tentang proses penanaman sayur di pertanian organik. Dari analisis data dapat diketahui adanya peningkatan kesadaran dan kepedulian para mahasiswa terhadap lingkungan alam setelah mereka melakukan tugas lapangan dan timbul harapan untuk berpartisipasi dalam pemeliharaannya.